When language teacher emotions and language policy intersect: A critical perspective. (April 2022) - Her, Lee; De Costa, Peter I.
Abstract: This case study investigates how one community college instructor in California navigated a set of rules regarding how teachers should feel – feeling rules (Zembylas, 2006) – at the workplace, imposed by a new language policy to accrue emotional capital, embodied emotions developed over time through power structures and daily interaction with students and faculty. A post-structurally oriented emotion and emotional capital framework was adopted to highlight the unequal power relations between the institution and teachers. Our study, which drew on data from a questionnaire, interviews, observations and policy documents, revealed that our focal participant, Alan, was able to align with the feeling rules and manage his emotion labor by employing different strategies (i.e., spirituality and empathy). Instead of resisting the feeling rules or avoiding the emotion labor that stemmed from his workplace, he actively accrued emotional capital by developing tools for future work-related endeavors. The study ends with a call for more research on teacher's emotional capital in TESOL.